Penerapan Metode Dekomposisi Adomian Laplace Dalam Menentukan Solusi Persamaan Panas - Muhammad Abdy; Syafruddin Side; Reza Arisandi (Jurusan Matematika FMIPA UNM, 2018)
This study discusses the application of Adomian Laplace Decomposition Method (ALDM) in determining the solution of heat equation. Adomian Laplace Decomposition Method is a semi analytical method to solve nonlinear differential equations that combine Laplace transform and Adomian decomposition method. Based on the calculation result, Adomian Laplace decomposition method can approach the settlement of ordinary nonlinear differential equations.